Four years of EZ-IO system in the preand in-hospital emergency setting - Reinhardt, Lars; Brenner, Thorsten; Bernhard, M.; Knapp, Jürgen; Sikinger, M.; Martin, Eike; Helm, M.; Popp, Erik (Central European journal of medicine, 2013)
Der Artikel Four years of EZ-IO® system in the preand in-hospital emergency setting wurde am 1. April 2013 in der Zeitschrift Open Medicine (Band 8, Heft 2) veröffentlicht.
Im Titel ist ® dargestellt
Gesehen am 21.12.2021